Influence of dietary carnitine and/or chromium on blood parameters of gestating sows - J C Woodworth; Michael D Tokach; S I Koo; J Ernest Minton; K Q Owen; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
Gestating sows (n=44; parity=2.0; BW=458 lb) were used to determine the effects of dietary Carnitine and/or chromium picolinate on daily blood parameter profiles. Diets were formulated as a 2 × 2 factorial with carnitine (0 or 50 ppm) and chromium (0 or 200 ppb) and were fed from breeding, through gestation, lactation, and 30 d into the next gestation at which time blood was collected. Sows were fed one meal per day during gestation (2.1 kg) and ad libitum during lactation. Sows were fitted with indwelling venous catheters and blood (plasma) was collected at feeding, once every 15 min for the first 3 h after feeding, and at 6, 9, 15, 20, and 24 h after feeding. Chromium picolinate elicited its greatest effect immediately after feeding (0-3 h) by decreasing (P0.10); however, sows fed carnitine had numerically higher (P=0.11) IGF-1 and IGFBP-3 (P=0.06). In summary, the changes in metabolites and metabolic hormones indicate that both carnitine and chromium influence energy metabolism of gestating sows; however, their effects on blood parameters are different. Thus, the improvement in energy status from adding both carnitine and chromium may have an additive effect on reproductive performance of sows.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Sows; Carnitine; Chromium; Blood Parameters; Swine